O -Benzoquinone and Ester-Linked Hydroxyfatty Acid as Additional Compounds from Lonchocarpus nicou - Ata Martin Lawson (Open Journal of Plant Science - Peertechz Publications, 2016)
New o-benzoquinone and a C16 long-chain para-coumarate ester were isolated from Lonchocarpus nicou roots. Their structural elucidations are based on different spectroscopic data analysis. In addition, the known pterocarpanoids maackiain and flemichapparin-B never reported in L. nicou were also isolated along with rotenone, the major phytochemical from this tropical liana.